Strategy of Natural Disaster Management of Rob In Tanjung Emas Port Area Based on Value Engineering Analysis and Stakeholder Expectations - Prosis Setiyawan; Slamet Imam Wahyudi; Kartono Wibowo (International Conference on Coastal and Delta Areas, 2017)
Tanjung Emas Port was inaugurated by the government in 1985 and became the main entrance of export and import goods to and from Semarang. So many big companies are building their factories in this area. There is even an industrial estate called Tanjung Emas Processing Zone (TEPZ) which some companies enter in bonded zone. Yet this port faces an ever-present problem, namely rob coming from tidal water and also a continuous decline in soil surface. In order to protect the various port facilities, it is necessary to create a robust flood handling system that is economical, efficient and accurate. The aim of this research is to get the result of handling of inundation based on value engineering analysis and the best stakeholder expectation. Value engineering research approach is directed to the analysis of a function that is a way to get or know the functions that are not needed. The function is presented in the comparison of Cost and Worth. VE analysis in this study was conducted by comparing the handling of rob disasters between polder systems with road elevation. Analytical techniques used include information stage, functional analysis phase, creative phase, evaluation phase, development stage and presentation stage. Keywords: rob handling, value engineering, stakeholder expectations, Tanjung Emas port